Social Responsibilities of Business Managers - Hay, Robert D.; Gray, Ed R (Academy of Management Journal, 1974)
The authors contend that value systems and styles of social responsibility of managers have gone through three historical phases?Phase I, the profit maximizer style; Phase II, the trusteeship style; and Phase III, the quality of life style. Phase III values will become more accepted by business managers of the future.